Difﬁculties in being responsible institutional investors: evidence from Malaysia - Annuar, Hairul Azlan (Emerald, 2020)
Purpose – The purpose of this paper is to ascertain whether institutional investors in Malaysia faced limitations when they are involved in the corporate governance of their investee companies. Design/methodology/approach – A qualitative approach, consisting of a series of interviews with senior investment managers of different type of institutional investors, was chosen. In total, 18 interviews were conducted over a period of two months, which is thought to sufficiently provide the answers to the researchpurpose. Findings – The interviews revealed there are difficulties in monitoring all investee companies due to lack of time and resources. Traditional measures such as company financial performance and dividend policy, continued to befavored andrigorously monitored. The overdependence on hard criteriamay bea resultofa cultureofoverlyrewardingbeneficiariesand alackofexpertiseinbeinginvolvedinspecialized company areas such as strategy. Strict regulations hamper effort to be more involved in governing investeecompanies. Research limitations/implications – The research used interviews and generalization may become an issue. In addition, access to many managers depended on recommendations, and the respondents are selectedtorepresentthedifferenttypesofinstitutionalinvestors. Originality/value – Investigation into factors that may limit institutional investors’ involvement in corporate governance in Malaysian public listed companies, especially from a more qualitative viewpoint, is lacking. In addition, this paper advances the understanding of shareholder activism by addingtotheliteraturebyexploringtheissueinaspecificemergingmarketscontext.